Initial Clinical Experience of MR-Guided Radiotherapy for Non-Small Cell Lung Cancer - Crockett, Cathryn B.; Samson, Pamela; Chuter, Robert; Dubec, Michael; Faivre-Finn, Corinne; Green, Olga L.; Hackett, Sara L.; McDonald, Fiona; Robinson, Clifford; Shiarli, Anna-Maria; Straza, Michael W.; Verhoeff, Joost J. C.; et al. (Frontiers in Oncology, 2021)
Curative-intent radiotherapy plays an integral role in the treatment of lung cancer and therefore improving its therapeutic index is vital. MR guided radiotherapy (MRgRT) systems are the latest technological advance which may help with achieving this aim. The majority of MRgRT treatments delivered to date have been stereotactic body radiation therapy (SBRT) based and include the treatment of (ultra-) central tumours. However, there is a move to also implement MRgRT as curative-intent treatment for patients with inoperable locally advanced NSCLC. This paper presents the initial clinical experience of using the two commercially available systems to date: the ViewRay MRIdian and Elekta Unity. The challenges and potential solutions associated with MRgRT in lung cancer will also be highlighted.